Conservative management of retained products of conception in the normal placental position: A retrospective observational study. (September 2019) - Takahashi, Hironori; Ohhashi, Mai; Baba, Yosuke; Nagayama, Shiho; Ogoyama, Manabu; Horie, Kenji; Suzuki, Hirotada; Usui, Rie; Ohkuchi, Akihide; Matsubara, Shigeki
Abstract: Objectives: To clarify the outcome of retained products of conception (RPOC) without placenta previa. Study design: This was a retrospective cohort study consisting of 59 patients who abdominally or vaginally gave birth to infants after 14 weeks without placenta previa and had RPOC between April 2006 and December 2018. Patients' background, characteristics, and outcomes were compared between those requiring and not-requiring intervention for RPOC. Results: Of the 59 patients, pregnancies after assisted reproductive technology accounted for 18 (31%). The ultrasound-measured RPOC length was 4 cm (median) and 39 (66%) showed hypervascularity within RPOC. Interventions were required in 36 patients (61%), with all due to bleeding-related events. Multivariate regression analyses revealed that the interventions were significantly more likely in the following situations: younger than 35 years (aOR: 4.2, 95%CI: 1.1–18.5), RPOC length ≥4 cm (aOR: 8.6, 95%CI: 2.4–39.2), and RPOC hypervascularity (aOR: 4.6, 95%CI: 1.3–18.8). Methotrexate was administered to 8 patients, of whom 4 (50%) required further hemostatic interventions. Conclusion: In patients with RPOC without previa, 61 and 39% did and did not require hemostatic interventions, respectively. In the latter, a wait-and-see strategy resulted in the resolution of RPOC. Patients with larger RPOC (≥4-cm fragment length) and hypervascularity were significantly more likely to require hemostatic intervention.